Relationship between maternal and foetal glycemia and foetal endocrine pancreas in alpacas - Huaynates O., Johan (2016)
The aim of this study was determine the relationship between maternal glycemia with foetal glycemia and development of foetal endocrine pancreas. Eighteen pregnant alpacas and their respective foetus were grouped in the three thirds of the gestation period (n = 3, 4 and 11 for first, second and third third respectively). The relationship between levels of maternal glycemia and the levels of foetal glycemia, number of Langerhans islets (IL) per area (N°IL/mm2) and diameter of IL were of r: 0.98, 0.99, 0.93, respectively. Levels of maternal-foetal glucose, N°IL/mm2 and IL diameter were significantly higher (p<0.001) in the last third of gestation. The results would show that maternal glycemia affects the development of foetal endocrine pancreas.